The remarkable consumer experience of brands as drivers to a deep consumer-brand relationship - Loureiro, S. M. C. (Psychology of Branding, 2013)
This chapter reviews concepts of brand experience, brand connection, brand love and positive emotions, and the willingness to sacrifice in different perspectives. Then a theoretical model is proposed for explaining the mechanism under the extreme connection to a brand that leads to the willingness to sacrifice. The sacrifice for a brand means to give up one’s immediate self-interest or interests not related to the purchase and experience the brand for the sake of a relationship with the brand. The chapter concludes with suggestions to test the model and presents some preliminary empirical results from the first seminal studies.